Characteristics of Generating Carbon Oxides at Low-temperature Oxidation Stages of Low-Rank Coal - Yimeng Song (Shock and Vibration)
Coal oxidation leads to coal fires prone to coal geohazard accidents. However, studies on carbon oxide gases being indicator gases in predicting spontaneous combustion of coal remain in the initial stage. To better investigate the stage characteristics of generating carbon oxide gases in the low-temperature oxidation process of coal, this study adopts STA-FTIR to experimentally determine the coal weight variation and exothermic condition and the generation law during the low-temperature oxidation process of coal (30–350°C). And, by employing the DFT method, the study determines the chemical reaction and activation energy generated by carbon oxide gases in coal molecules and ascertains the reaction characteristics at different temperatures. The research results indicate that the low-temperature oxidation phase of coal is divided into four main phases, namely, the physical-chemical adsorption phase, the desorption phase, the dynamic equilibrium phase, and the oxidative adsorption phase, each of which has different characteristics for the production of carbon-oxygen compounds, which is important for the prediction of coal spontaneous combustion and the prevention of coal geological disasters.